Engineering Projects in Community Service (EPICS) in High Schools: Subtle but Potentially Important Student Gains Detected from Human-Centered Curriculum Design - Alissa Ruth; Joseph Hackman; Alexandra Brewis; Tameka Spence; Rachel Luchmun; Jennifer Velez; Tirupalavanam G. Ganesh (Education Sciences, 2019)
A major goal in Engineering training in the U.S. is to continue to both grow and diversify the field. Project- and service-based forms of experiential, problem-based learning are often implemented with this as a goal, and Engineering Projects in Community Service (EPICS) High is one of the more well-regarded and widely implemented. Yet, the evidence based on if and how participation in such programs shapes student intentions and commitment to STEM pathways is currently limited, most especially for pre-college programming. This study asks: How do high school students’ engineering mindsets and their views of engineering/engineers change as they participate in project⁻service learning (as implemented through an EPICS High curriculum)? This study employed a mixed method design, combining pre- and post-test survey data that were collected from 259 matched students (63% minority, 43% women) enrolling in EPICS High (total of 536 completed pre-tests, 375 completed post-tests) alongside systematic ethnographic analysis of participant observation data conducted in the same 13 socioeconomically diverse schools over a two-year period. Statistical analyses showed that participants score highly on engineering-related concepts and attitudes at both pre- and post-test. These did not change significantly as a result of participation. However, we detected nuanced but potentially important changes in student perspectives and meaning, such as shifting perceptions of engineering and gaining key transversal skills. The value of participation to participants was connected to changes in the meaning of commitments to pursue engineering/STEM.